Less aid proliferation and more donor coordination? The wide gap between words and deeds - I\~naki Aldasoro; Peter Nunnenkamp; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2009)
We present a two-step approach of assessing whether major donors of foreign aid have met recent demands for less proliferated and better coordinated aid efforts. First, we calculate Theil indices revealing the concentration of each donor's aid on recipient countries and specific aid sectors. Second, we map overlaps of aid from different donors and over time to analyze the degree of coordination. Our results point to a wide and persistent gap between the rhetoric of political declarations and the donors' actual aid allocation during the period 1995-2006. Few donors have specialized on a limited set of recipients and aid sectors, and coordination has remained elusive.
Keywords: F35; 330; Aid allocation; sector-specific commitments; Theil index; donor coordination; overlaps; Entwicklungshilfe; Internationale Wirtschaftshilfe; Entwicklungskooperation; Internationale Zusammenarbeit; OECD-Staaten-seitig; Schätzung; Welt; Entwicklungsländer; OECD-Staaten